Recurrent Nevus Phenomenon Developing within a Keloid - Cody J. Rasner; Yan Zhou; Alessio Giubellino (MDPI AG, 2023)
The recurrent nevus phenomenon represents the persistence of a nevus within a scar from a prior biopsy site, with the acquisition of clinical and histologic features frequently overlapping with those of melanoma, posing relevant diagnostic challenges. Similar features are recognized in nevi that have undergone recent or chronic trauma and in sclerosing nevi. Any type of nevus may be subject to this phenomenon. Keloids are exuberant scars with an exaggerated accumulation of dense dermal collagen. Here we report a case of a 42-year-old woman with the incidental finding of an atypical melanocytic proliferation developing within a keloidal scar. The patient presented with a progressively enlarging auricular lesion three years after a piercing procedure. Upon histological examination, attentive scrutiny of the margin revealed an atypical compound melanocytic proliferation, predominantly single-celled at the junction but occasionally nested, with cytologic atypia and architectural disorder. This atypical proliferation was found emerging above a keloid. We interpreted the lesion as an atypical melanocytic lesion with features resembling the recurrent nevus phenomenon. This case raises awareness in recognizing these melanocytic lesions as benign, thereby avoiding overdiagnosis and unnecessary treatment.